Post‐fire vegetation recovery at forest sites is affected by permafrost degradation in the Da Xing'an Mountains of northern China. (5th August 2019) - Shi, Liang; Dech, Jeffery P.; Liu, Hongyan; Zhao, Pengwu; Bayin, Delehei; Zhou, Mei
Abstract: Question: Vegetation recovery and succession patterns after fire are not completely explained by the interactions of climate, disturbance, and species pool. Site‐specific factors can substantially change vegetation succession. We hypothesize that on sites exposed to fire and surface permafrost degradation, successional trajectories will produce different species assemblages than typical post‐fire succession. Location: Da Xing'an Mountains, northern China. Methods: Vegetation and environmental data were collected at eight sites of past natural wildfire events. These sites represented different topographical situations, with four sites on slopes (lacking surface permafrost) and four sites in valleys (with surface permafrost). Three plots were established on each site, representing three different fire presence zones (burned, ecotone and unburned areas), giving a total of 24 plots. We used non‐metric multidimensional scaling (NMS) to describe post‐fire vegetation recovery at different sites and multi‐response permutation procedures (MRPP) to test our hypothesis. Results: The variation in dates of last fire was similar between the slope and valley sites. Slope sites that had been burned prior to 2003 had recovered to a composition similar to unburned sites by the time the study was conducted in 2017. However, none of the burned valley sites had fully recovered, even those exposed to fire in 1986, suggesting that the surface permafrost conditions affected the recovery pattern of vegetation. On burned valley sites, shrub species that are tolerant of saturated soils had become dominant and the number of tree saplings and seedlings became significantly lower than on the slope sites. Conclusion: The interaction of fire and topographic site type (through the influence of surface permafrost degradation) was revealed as a primary factor affecting species composition and tree density of post‐fire communities. On valley sites, melting of the surface permafrost after fire caused a failure of tree recruitment and prompted shrub species tolerant of saturated soils to become dominant. Abstract : Slope and valley sites have different pathways to vegetation recovery after a forest fire. On slope sites, the recovery time effect weakens the effect of the fire, but at valley sites this effect does not occur within the time limits of this study. This lack of recovery appears to be related to the presence of surface permafrost in the valleys.